2017
DOI: 10.1016/j.clim.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells in inflammatory heart disease

Abstract: Despite of a multitude of excellent studies, the regulatory role of natural killer (NK) cells in the pathogenesis of inflammatory cardiac disease is greatly underappreciated. Clinical abnormalities in the numbers and functions of NK cells are observed in myocarditis and inflammatory dilated cardiomyopathy (DCMi) as well as in cardiac transplant rejection [1–6]. Because treatment of these disorders remains largely symptomatic in nature, patients have little options for targeted therapies [7, 8]. However, blocka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 157 publications
(164 reference statements)
2
75
0
Order By: Relevance
“…NK cells account for over 1% of cardiac lymphocytes and participate to the regulation of process involved in cardiac diseases [ 181 ]. In patients with coronary artery diseases (CAD), NK cells have been found to be decreased in number and function, but not altered in their phenotype [ 182 ].…”
Section: Innate Immunity Cells Contribution To Cardiac Fibrosismentioning
confidence: 99%
“…NK cells account for over 1% of cardiac lymphocytes and participate to the regulation of process involved in cardiac diseases [ 181 ]. In patients with coronary artery diseases (CAD), NK cells have been found to be decreased in number and function, but not altered in their phenotype [ 182 ].…”
Section: Innate Immunity Cells Contribution To Cardiac Fibrosismentioning
confidence: 99%
“…Rose et al suggested that the immunopathogenesis of this myocarditis model has three different stages: (i) induction of pathogenic autoimmunity from virus infection; (ii) development of myocardial inflammation; and (iii) progression to dilated cardiomyopathy. Each of the three stages has a cytokine signature and inflammatory cell profile that mirrors and modulates the quantity and quality of inflammation and healing …”
Section: Animal Modelsmentioning
confidence: 99%
“…However, their activation could also cause autoaggression and inflammation if the host's autologous cells become stressed/infected and become more susceptible to NK cell-mediated killing. Blocking of one or more NK cell activating receptors may alleviate disease progression as has been demonstrated in cardiac inflammation [76]. However, further studies are required to test the relevance of such an approach in CD patients.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%